PERSISTENT TOXICITY OF SOME INSECTICIDES AGAINST DIAMOND BACK MOTH, PLUTELLA XYLOSTELLA (LINN.) ON CABBAGE - SHUKLA, ABHISHEK; KUMAR, ASHOK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Persistent toxicity of various pesticides on cabbage leaves were tested against 3rd and 4th instar larvae of P. xylostella. Maximum persistent residual toxicity wass recorded for betacyfluthrin (750 ml/ha) (PT=805.0 and 770.0)) against both thesse instars, respectively. Azadiraçtin (1.5 lit/ha) had the shortest persistent toxicity against both the instars (PT=134.35 and 140.62). Residues of betacyfiuthriu (750 ml/ha) were noticed upto 15 days, while for azadirachtin (1.5 lit/ha) it was noticed upto 5 days.